2015
DOI: 10.1039/c5fd00049a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and economic analysis of reactive capture of dilute carbon dioxide with Grignard reagents

Abstract: Carbon Dioxide Utilisation (CDU) processes face significant challenges, especially in the energetic cost of carbon capture from flue gas and the uphill energy gradient for CO2reduction. Both of these stumbling blocks can be addressed by using alkaline earth metal compounds, such as Grignard reagents, as sacrificial capture agents. We have investigated the performance of these reagents in their ability to both capture and activate CO2directly from dried flue gas (essentially avoiding the costly capture process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…27 In this report we demonstrate the capability of simple metal halides-based catalysts to convert the CO 2 from diluted flows to cyclic carbonates under semibatch conditions. 28 With the catalytic and kinetic data at hand, the opportunity and the limitations of employing a flow of industrial flue gas as an impure CO 2 source for the synthesis of cyclic organic carbonates are assessed by employing the most active catalytic system. Thus, the first direct application of industrial flue gas for the synthesis of cyclic carbonates and, in general, the first application of flue gas in catalysis under ambient conditions is reported.…”
mentioning
confidence: 99%
“…27 In this report we demonstrate the capability of simple metal halides-based catalysts to convert the CO 2 from diluted flows to cyclic carbonates under semibatch conditions. 28 With the catalytic and kinetic data at hand, the opportunity and the limitations of employing a flow of industrial flue gas as an impure CO 2 source for the synthesis of cyclic organic carbonates are assessed by employing the most active catalytic system. Thus, the first direct application of industrial flue gas for the synthesis of cyclic carbonates and, in general, the first application of flue gas in catalysis under ambient conditions is reported.…”
mentioning
confidence: 99%
“…Overall, the presence of small quantities of water would primarily serve to only reduce reaction yield. Previous work carried out by our group has indicated that the reaction of Grignard reagents with oxygen is relatively slow compared to its reaction with CO2, although flue gas streams with very high oxygen levels may see trace amounts of the oxygen products, MgO, methanol, and possibly dimethyl ether (Goebel and Marvel, 1933;Dowson et al, 2015).…”
Section: The Cost Of Carbon Capturementioning
confidence: 99%
“…Previous work carried out by this group has identified organometallics and particularly Grignard reagents as being suitable for the direct conversion of flue gas concentration of CO2 into value-added products such as acetic, terephthalic, and adipic acids (Dowson et al, 2015). The organomagnesium reagent, which was shown to react readily with CO2, even at low partial pressures, can then be regenerated from the by-product magnesium dihalide (MgX2).…”
Section: The Cost Of Carbon Capturementioning
confidence: 99%
“…An alternative approach, investigated previously by the authors, used sacrificial Grignard reagents to capture and convert CO 2 directly from the gas phase to a range of potentially valuable carboxylic acid products under room temperature conditions. 8 Since the by-product of the reaction, the magnesium dihalide, is the commercial feedstock for highly efficient magnesium production by electrolysis, in principle the sacrificial Grignard reagent could be regenerated. 9 This approach would combine the capture and conversion of the CO 2 into a single exothermic room-temperature process, which would allow the overall conversion of an alcohol into the carboxylic acid of the next member of the homologous series, with a carbon chain one atom longer than the starting alcohol ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%